Reclaiming economics for future generations - Ambler, Lucy (Manchester capitalism., 2022)
Reclaiming economics for future generations argues that to build economies which serve people and the planet we need a diverse and decolonised curriculum. How does the global economy currently fail people and the planet, and why has mainstream economics knowledge inadequately addressed the pressing issues of today?